2003
DOI: 10.1038/sj.gt.3301938
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble lipopolymer as an efficient carrier for gene delivery to myocardium

Abstract: Water-soluble lipopolymer (WSLP), which consisted of polyethylenimine (PEI, 1800 Da) and cholesterol, was characterized as a gene carrier to smooth muscle cells and myocardium. Acid-base titration showed that WSLP had a proton-buffering effect. The size of WSLP/plasmid DNA (pDNA) complex was around 70 nm. WSLP/pDNA complex was transfected to A7R5 cells, a smooth muscle cell line. WSLP showed the highest transfection at a 40/1 N/P ratio. WSLP has higher transfection efficiency than PEI (1800 and 25 000 Da), Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 41 publications
2
102
0
Order By: Relevance
“…Previous work in our lab using water soluble lipopolymer (WSLP) produced significantly higher gene expression than naked pDNA and bPEI/pDNA in the same model [36]. WSLP also mediated higher transgene expression in ischemic rabbit myocardium as apposed to healthy myocardium using the hypoxia inducible pEpo-SV-VEGF plasmid [23].…”
Section: In Vivo Delivery Of Ss-paed/rtp-vegf In Ischemic Myocardiummentioning
confidence: 71%
See 1 more Smart Citation
“…Previous work in our lab using water soluble lipopolymer (WSLP) produced significantly higher gene expression than naked pDNA and bPEI/pDNA in the same model [36]. WSLP also mediated higher transgene expression in ischemic rabbit myocardium as apposed to healthy myocardium using the hypoxia inducible pEpo-SV-VEGF plasmid [23].…”
Section: In Vivo Delivery Of Ss-paed/rtp-vegf In Ischemic Myocardiummentioning
confidence: 71%
“…Previous work in our lab was performed by injecting 200 μg pDNA complexed with WSLP into rabbit myocardium [23,36]. We initially decided to perform dose response injections with our SS-PAED/RTP-VEGF system starting at 100 μg RTP-VEGF and then increasing the dose until VEGF expression was apparent.…”
Section: In Vivo Delivery Of Ss-paed/rtp-vegf In Ischemic Myocardiummentioning
confidence: 99%
“…The use of this polymer has been used to deliver genes to several different cancers, myocardium and corpus cavernosum. [45][46][47][48][49] In summary, we have demonstrated that ischemiainducible VEGF gene therapy improves the efficacy of VEGF gene therapy for myocardial infarction through decreased apoptosis and increased angiogenesis.…”
Section: Ischemia-inducible Gene Therapy Jw Yockman Et Almentioning
confidence: 88%
“…44,45 The WSLP gene carrier forms self-assembling lipopolymer/DNA complexes with the therapeutic gene. The multifunctional characteristics of these novel polymers include DNA condensation, protection of DNA integrity, cell membrane adhesion and endosomal disruption capabilities with minimal toxicity.…”
Section: Ischemia-inducible Gene Therapy Jw Yockman Et Almentioning
confidence: 99%
See 1 more Smart Citation